STRATEGI GURU DALAM MENGATASI BULLYING PADA SISWA KELAS V DI SEKOLAH DASAR KATOLIK DON BOSKO 4 KUPANG - Mariana Agustina Dillak; Kristina E. Noya Nahak; Yulsy Marselina Nitte (STKIP Subang, 2026)
Teachers’ Strategies in Addressing Bullying among Fifth Grade Students at Catholic Elementary School Don Bosko 4 Kupang. Undergraduate Thesis. Primary School Teacher Education Study Program, Faculty of Teacher Training and Education, Universitas Citra Bangsa Kupang. This study was motivated by the continued occurrence of bullying behavior among fifth grade students at Catholic Elementary School Don Bosko 4 Kupang, which negatively affects students’ psychological, social, and academic development and disrupts the learning process in the classroom. The study aimed to describe teachers’ strategies in addressing bullying and to explain the efforts made by teachers in creating a safe, comfortable, and inclusive learning environment for students. This research employed a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation, involving the principal, classroom teachers, and fifth grade students as research subjects. Data analysis used the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The results showed that forms of bullying included verbal bullying such as mocking, insulting, calling students by harsh nicknames, and making unfounded accusations, as well as nonverbal bullying in the form of physical actions such as pushing, hitting, pulling clothes, and taking classmates’ belongings. Teachers’ strategies were implemented through direct intervention, educational approaches based on moral values and empathy, the establishment of positive classroom rules, role modeling, and collaboration with parents and the school. The study concludes that teachers’ strategies play an important role in reducing bullying and supporting students’ socio-emotional development in a sustainable manner.